Are Cows Comfortable in Modern Dairy Facilities? - Izabella Toledo (EDIS)
The main challenge in modern large dairy farms is to achieve maximum milk production while maintaining optimal cow health and welfare. Facilities should be designed to assure that calves, heifers and cows are comfortable and can successfully grow and develop in order to reach peak performance. It is crucial to provide dairy cattle with basic shelter needs and allow farm staff to manage these animals in an effective manner. In addition, cows need to accomplish certain natural behavioral activities daily. Some factors that may decrease or limit the ability of cows to express natural behaviors include but are not limited to resting area and resting behavior, time spent away from pen (i.e. for milking and other management procedures), feed and water access and availability, stocking density, and environmental factors such as heat stress. Understanding cows needs and their natural behaviors allows us to adjust facilities in order to optimize cow comfort and subsequent productivity and profitability.